LEGAL PROTECTION TO WOMEN WITH DISABILITIES AS VICTIMS OF SEXUAL VIOLENCE AT THE CIQAL FOUNDATION YOGYAKARTA - Subekti, Subekti; Annisa, Dea (Yustisia, 2017)
The purpose of this research is to know the forms of legal protection to women with disabilities as victims of sexual violence on the CIQAL Foundation and to know obstacles that occur in the legal protection process. This research is an empirical law research that is both descriptive by qualitative approaches. Location of the research at the CIQAL Foundation Yogyakarta.Based on the results of the research, it is got the data since 2014 until 2016, CIQAL has noted there were seventy six of violence cases against women with disabilities in Yogyakarta region and sixty cases there are sexual violence. From the sixty cases of sexual violence only three cases have got judicial process. Not processing of legal, cause of the victims can not get the justice and their rights as the victims and also the perpetrators of violence have potential to do the violence again. The matter CIQAL efforts to give the legal protection to women with disabilities as victims of sexual violence get their rights. The legal protection is given the legal colleague and non the colleague by the CIQAL Foundation Yogyakarta. There are some obstacles when the foundation gives doing the legal protection process. The obstacles which are divided by two, internal victims factors that includes the limitation which owned the victims, and the victims family; external victims factors that includes the problem in the legal scope, and the society.